Given a triangle $ABC$ with angles a,b & c, prove that if $\sin^2(a) + \sin^2(b) + \sin^2(c) = 2$ then the triangle is right angled (has an angle of $90^o$).

If I assume the triangle is right angled and have AB, AC and BC as sides, with BC being the base, then I can say that statement is true, since $\sin^2(a)$ would be 1 where $a=90^o$.

Also, since it's a right angled triangle we can say that $\sin^2(b) = AC^2/BC^2$ and $\sin^2(c) = AB^2/BC^2$. The sum of $\sin^2(b) + \sin^2(c)$ would be equal to $(AC^2+AB^2)/BC^2$ which is 1 (pythagoras theorem). Hence the sum of squares of sines of all 3 angles is indeed 2.

But how do I prove this? As in, I'm only given the starting equation, how do I get from there to a right angled triangle?

  • $\begingroup$ Note that, $\sin^2b=\cos^2a+\cos^2c$ or any other combination. $\endgroup$ – Mann Jun 15 '15 at 12:27
  • $\begingroup$ i think you mean $sin^2(c) = AB^2/BC^2$ and not $sin(c) = AB^2/BC^2$ $\endgroup$ – supinf Jun 15 '15 at 12:36
  • 1
    $\begingroup$ Yup, thanks for the catch, that's what I meant. Fixed now. $\endgroup$ – MikhaelM Jun 15 '15 at 12:38

Notice, in $\Delta ABC$ , we have $a+b+c=180^o$

Given that $$\sin^2 a+\sin^2 b+\sin^2 c=2$$ $$\implies \sin^2 a+\sin^2 b+\sin^2 (180^o-(a+b))=2$$ $$\implies \sin^2 a+\sin^2 b+\sin^2 (a+b)=2$$ $$\implies (\sin a\cos b+\cos a\sin b)^2=2-\sin^2 a-\sin^2 b$$ $$\implies \sin^2 a\cos^2 b+\cos^2 a\sin^2 b+2\sin a\sin b\cos a\cos b=\cos^2 a+\cos^2 b$$ $$\implies -(1-\sin^2 a)\cos^2 b-(1-\sin^2 b)\cos^2 a+2\sin a\sin b\cos a\cos b=0$$ $$\implies -\cos^2 a\cos^2 b-\cos^2 a\cos^2 b+2\sin a\sin b\cos a\cos b=0$$ $$\implies -2\cos a\cos b(\cos a\cos b-\sin a\sin b)=0$$ $$\implies \cos a\cos b\cos(a+b)=0$$ $$ \color{blue}{\text{if } \quad \cos a=0 \implies a=90^o}$$ $$ \color{blue}{\text{if } \quad \cos b=0 \implies b=90^o}$$ $$ \color{blue}{\text{if } \quad \cos (a+b)=0 \implies a+b=90^o \iff c=90^o}$$ We find that above three cases show that $\color{blue}{\Delta ABC}$ is $\color{blue}{\text{right angled}}$.

  • $\begingroup$ Just checked your response and I find it really really good! Thanks for the reply, this solution is really good and easy to follow. $\endgroup$ – MikhaelM Jun 28 '15 at 13:54
  • $\begingroup$ It's worth noting that, since $a+b+c=180^\circ$, then $\cos(a+b) = -\cos c$. $\endgroup$ – steven gregory Jan 23 '17 at 15:28

We have: $$\sin^2 A + \sin^2 B+\sin^2 C = 3-\sum_{cyc}\cos^2 A =\frac{1}{2}\left(3-\sum_{cyc}\cos(2A)\right)$$ hence $LHS=2$ is equivalent to $\sum_{cyc}\cos(2A)=-1$ or to: $$ \cos^2 A+\cos(B+C)\cos(B-C) = 0 \tag{1}$$ but since $A+B+C=\pi$, $\cos(B+C)=\cos(\pi-A)=-\cos(A)$ and the previous line is equivalent to: $$ \cos(A)=\cos(B-C)\quad\text{or}\quad \cos(A)=0,\tag{2} $$ so $A=\frac{\pi}{2}$ or: $$ -\cos(B)\cos(C)+\sin(B)\sin(C) = \cos(B)\cos(C)+\sin(B)\sin(C)\tag{3}$$ that gives $\cos(B)\cos(C)=0$.

  • $\begingroup$ I don't quite understand your first line. What does that sum mean? $\endgroup$ – MikhaelM Jun 15 '15 at 12:49
  • $\begingroup$ @MikhaelM: $\sum_{cyc}\cos^2 A$ is just a shorthand notation for $\cos^2 A+\cos^2 B+\cos^2 C$. $\endgroup$ – Jack D'Aurizio Jun 15 '15 at 13:09
  • $\begingroup$ Thank you! Your solution is the easiest to understand, at least for me. $\endgroup$ – MikhaelM Jun 15 '15 at 14:56


Method $\#1:$

Using Prove that $\cos (A + B)\cos (A - B) = {\cos ^2}A - {\sin ^2}B$,


Method $\#2:$ Alternatively using Double angle & Prosthaphaeresis formula ,


Now $\cos(A+B)=\cos(\pi-C)=-\cos c$

$\implies F=2-[-\cos C\cos(A-B)+\cos^2C]$

$=2-\cos C[-\cos(A-B)+\cos C]$

$=2-\cos C[-\cos(A-B)-\cos(A+B)]$ as $\cos(A+B)=-\cos c$

$$\implies\sin^2A+\sin^2B+\sin^2C=2+\cos C[2\cos A\cos B]$$

Can you reach home from here?


$$\sin(a)=\sin(\pi-b-c)=\sin(b+c),$$ Then with obvious shorthands, $$\begin{align}0&=2-s_a^2-s_b^2-s_c^2\\ &=c_b^2+c_c^2-s_a^2\\ &=c_b^2+c_c^2-(s_a c_b+c_a s_b)^2\\ &=c_b^2+c_c^2-s_b^2c_c^2-2s_b c_b c_c s_c-c_b^2s_c^2\\ &=c_b^2c_c^2+c_b^2c_c^2-2s_b c_b c_c s_c\\ &=2c_b c_c(c_b c_c-s_b s_c)\\ &=2c_bc_cc_{b+c}.\end{align}$$

The product is null with one of $$b=\frac\pi2,$$ $$c=\frac\pi2,$$ $$b+c=\pi-a=\frac\pi2.$$

  • 1
    $\begingroup$ i think he is asking for the other direction $\endgroup$ – supinf Jun 15 '15 at 12:34
  • $\begingroup$ @supinf: you are quite right, I am trying to fix. $\endgroup$ – Yves Daoust Jun 15 '15 at 12:36
  • 1
    $\begingroup$ I think this just proves that my sum is 2 in a right angled triangle. I think I need to prove that if the sum is 2, then the triangle is right angled. $\endgroup$ – MikhaelM Jun 15 '15 at 12:39
  • $\begingroup$ @MikhaelM: I have updated. $\endgroup$ – Yves Daoust Jun 15 '15 at 13:25

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.